The Mediating Role of Perceived Social Support Between Resilience and Anxiety 1 Year After the COVID-19 Pandemic: Disparity Between High-Risk and Low-Risk Nurses in China - Hou, Tianya; Yin, Qianlan; Xu, Yan; Gao, Jia; Bin, Lian; Li, Huifen; Cai, Wenpeng; Liu, Ying; Dong, Wei; Deng, Guanghui; Ni, Chunyan (Frontiers in Psychiatry, 2021)
Introduction: One year after the Coronavirus disease 2019 (COVID-19) outbreak, China has made substantial progress in the prevention and control of the pandemic, while the epidemic situation remains grim in China since virus may easily survive with the falling temperature in winter. The present study aimed to compare the prevalence and associated factors of anxiety between high-risk and low-risk nurses one year after the COVID-19 outbreak, and examine the association between resilience and anxiety and its underlying mechanisms. Method: Connor-Davidson Resilience scale, Perceived Social Support Scale and Generalized Anxiety Disorder Scale were administrated to 701 nurses from Jiangsu Province, China, one year after the COVID-19 outbreak. The mediating effect was examined by Mackinnon’s four-step procedure, while the moderated mediation model was tested by Hayes PROCESS macro. Results: The findings presented the prevalence of anxiety among nurses was 21.4% one year after the COVID-19 pandemic. High-risk nurses presented a higher prevalence of anxiety (24.5% vs. 19.3%) than low-risk nurses. Gender, age and professional title were significantly associated with anxiety only in high-risk nurses (all P < 0.05). Perceived social support mediated the association between resilience and anxiety and the indirect effect was stronger for high-risk nurses than low-risk nurses. Conclusion: Anxiety remains prevalent among nurses one year after the COVID-19 outbreak, and resilience plays a protective role against anxiety. Programs that enhance resilience and social support should be designed and special attention should be paid to nurses from high-risk units.